Comparative Analysis of Mothers' Anxiety Levels Regarding the Implementation of the Covid-19 Vaccine in Elementary School-aged Children in Sumbawa Regency - Herni Hasifah; Abdul Hamid; Iga Maliga (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2022)
Background: The current COVID-19 pandemic has triggered changes in people's lives and forced the government to implement various policies to overcome the spread of COVID-19 in Indonesia. One of the programs initiated to overcome COVID-19 is to seek community immunity (herd immunity) through the Covid-19 vaccination program. However, the government's COVID-19 vaccination program is still experiencing obstacles due to the large amount of information related to the vaccine itself, which triggers public anxiety and various perceptions. Regional differences also help health workers to engage the community. Especially for children. Objective: The problem in this study is how the level of anxiety associated with vaccination of children in the area is compared with the anxiety of mothers in the coastal area. The purpose of this study was to describe parental anxiety related to child vaccination and to compare the anxiety conditions of parents in urban and coastal areas in Sumbawa Regency. Methods: This research uses quantitative research with a comparative study approach. The samples in this study were mothers and children who had undergone COVID-19 vaccination in urban and coastal areas. The sample that meets the research criteria is 80 respondents who are determined by purposive sampling technique which is divided into 2 areas. Results: Based on the results of statistical tests using the Man Whitney Test using SPSS version 16.0, it is known that the significant value obtained is 0.096. Conclusion: There is no significant difference showing the anxiety of parents living in urban and coastal areas in Sumbawa Regency.